2009
DOI: 10.1159/000236004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Remission of Specific IgE Aeroallergen Sensitization from Age of 40 to 60 Years, and Association with Alcohol Consumption

Abstract: Background: Data on incidence and long-term persistence of IgE aeroallergen sensitization in older adults are limited. Alcohol consumption is a strong immune-modulator with a significant impact on the IgE response. Objectives: We aimed to assess the incidence and remission of aeroallergen sensitization from the age of 40 to 60 years. Furthermore, we examined the relationship of alcohol consumption to the prevalence and incidence of aeroallergen sensitization. Methods: In 1976–1977, a total of 1,200 people born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…Thus in the middle-aged and elderly subjects, normal aging is assumed to affect the prevalence of allergic sensitization, and the lower prevalence in the elderly might not primarily be caused by a birth cohort effect, as suggested by others. 12,23 To the best of our knowledge, only a few longitudinal population-based studies among adults have reported data about the incidence and remission of allergic sensitization and a possible age effect. We found a cumulative incidence of 5%, and remission was 32% during a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in the middle-aged and elderly subjects, normal aging is assumed to affect the prevalence of allergic sensitization, and the lower prevalence in the elderly might not primarily be caused by a birth cohort effect, as suggested by others. 12,23 To the best of our knowledge, only a few longitudinal population-based studies among adults have reported data about the incidence and remission of allergic sensitization and a possible age effect. We found a cumulative incidence of 5%, and remission was 32% during a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies assessing the incidence and remission of allergic sensitization based on objective and physiological tests are even rarer. [12][13][14] The prevalence of allergic sensitization increases with age up to young adulthood, 3,14 whereas from middle age, the prevalence decreases with increasing age. 3,11 The decrease in prevalence among the elderly might be related to normal aging or a birth cohort effect.…”
mentioning
confidence: 99%
“…Furthermore, experimental animal studies [11,12] and observational studies in humans [13,14] strongly support the idea that alcohol consumption increases serum total IgE levels. In contrast, the relationship between alcohol consumption and specific IgE sensitization is less clear [15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that excess histamine release plays an important role in alcohol-induced asthma. Further studies are required to explore the mechanisms underlying this process, including how histamine localizes to target organs, the molecular mechanism associated with the actions of histamine, the roles of the nonhistamine chemical mediators that are released from mast cells and basophils, and the characteristics of the immune system response in these patients [19,20]. Future potential research topics include the study of sensitized ALDH2-deficient mice and an assessment of the inhibitory effects caused by various agents.…”
Section: Discussionmentioning
confidence: 99%